Ilmu Hukum Berparadigma Pancasila di Era Globalisasi: Sebuah Tantangan Liberalisasi Ekonomi dan Teknologi - Indra Rahmatullah; Ika Atikah (Universitas Batanghari Jambi, 2022)
The liberalization of economy and technology in globalization cause philosophical problem to the jurisprudence paradigm in Indonesia because of its capitalism ideology which full of capital owners interests and monopolies that harm small and medium enterprises. Meanwhile, liberalization on technology which is considered free from any ideology, is not separable from capitalism which controls technological sophistication that causes the ideological disruption of a nation (new colonialism). The purpose of this study is to analyze the relevance of Pancasila which is the philosophical bases of the jurisprudence paradigm in Indonesia when faced the globalization. To analyze this problem, this article uses normative legal research method with philosophical approach. Pancasila as the guardian of the ideology of the Indonesia state has very strategic and significant role in maintaining the philosophy of law that is constantly evolving in responding the globalization from ontology, epistemology and axiology aspects. The five precepts of Pancasila are dynamic and accommodating ideological-philosophical bases for the development of jurisprudence in facing the current challenges.